Cover and Lug Optimization of Auxiliary Converter Based on OptiStruct Software - HE Yanfei; DING Jie (机车电传动)
Modal analysis of the high-frequency auxiliary converter for the metro was conducted with Ansys software, and according to the results, the cover vibration was most in the normal direction under the first-order vibration frequency of the auxiliary converter. In order to improve the stiffness of the cover, the enhancement of the first-order vibration frequency of the cover was taken as the target, and topography optimization of the auxiliary converter cover was carried out with the OptiStruct software. Besides, the topology optimization of the lug was also conducted to lighten the lug. With the results of the optimization, it was shown that the firstorder vibration frequency of the auxiliary converter was improved by 32%, and the weight of the lug was decreased by 21%, with an obvious optimization effect.